2020
DOI: 10.1073/pnas.2003346117
|View full text |Cite
|
Sign up to set email alerts
|

Wounding-induced changes in cellular pressure and localized auxin signalling spatially coordinate restorative divisions in roots

Abstract: Wound healing in plant tissues, consisting of rigid cell wall-encapsulated cells, represents a considerable challenge and occurs through largely unknown mechanisms distinct from those in animals. Owing to their inability to migrate, plant cells rely on targeted cell division and expansion to regenerate wounds. Strict coordination of these wound-induced responses is essential to ensure efficient, spatially restricted wound healing. Single-cell tracking by live imaging allowed us to gain mechanistic insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 46 publications
3
75
1
Order By: Relevance
“…DAMPs released from wounds signal the surrounding intact cells via Ca 2+ , ROS, phosphorylation, and electrical signaling to mount defense gene expression. Most likely, direct physical responses, such as changes in mechanical forces and cell pressure surrounding the wound, play a pronounced signaling role, although these are largely unknown ( Routier-Kierzkowska et al, 2012 ; Hoermayer et al, 2020 ). In parallel and depending on the severity of damage, systemic signals are propagated from the wound site to the rest of the plant, comprising leaf-to-leaf, root-to-root, leaf-to-root, and root-to-leaf signaling.…”
Section: Local Vs Systemic Wound Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…DAMPs released from wounds signal the surrounding intact cells via Ca 2+ , ROS, phosphorylation, and electrical signaling to mount defense gene expression. Most likely, direct physical responses, such as changes in mechanical forces and cell pressure surrounding the wound, play a pronounced signaling role, although these are largely unknown ( Routier-Kierzkowska et al, 2012 ; Hoermayer et al, 2020 ). In parallel and depending on the severity of damage, systemic signals are propagated from the wound site to the rest of the plant, comprising leaf-to-leaf, root-to-root, leaf-to-root, and root-to-leaf signaling.…”
Section: Local Vs Systemic Wound Signalingmentioning
confidence: 99%
“…Auxin accumulates within a day at the wound site and directly activates expression of the WUSCHEL related homeobox 11 ( WOX11 ) transcription factor, which works redundantly with WOX12 to enable the transition of the local cambium cells to root founder cells within 4 days following the cut ( Liu et al, 2014 ; Hu and Xu, 2016 ). Accumulating evidence from recent publications on root regeneration emphasizes the importance of auxin during the replenishment of a single cell, a cluster of damaged root cells, or even regeneration of a complete de novo root tip ( Canher et al, 2020 ; Hoermayer et al, 2020 ; Matosevich et al, 2020 ). Depending on the severity and type of damage, the mode of action that allows for sufficient auxin accumulation in order to facilitate the regeneration process varies.…”
Section: Wound-induced Hormone Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that regeneration of specific cell types in root was influenced by osmotic pressure, suggesting that mechanical signalling pathways can be instrumental in regeneration(Hoermayer et al , 2020). Therefore, it is possible that mechanical signals can instruct DNRR.…”
Section: Figurementioning
confidence: 99%